Prevalence of psychiatric disorders in infertile women and men undergoing in vitro fertilization treatment - Volgsten, H.; Skoog Svanberg, A.; Ekselius, L.; Lundkvist, Ö.; Sundström Poromaa, I. (Human reproduction (Oxford), 2008)
BACKGROUND This study was undertaken to determine the prevalence of psychiatric disorders in infertile women and men undergoing in vitro fertilization (IVF) treatment. METHODS Participants were 1090 consecutive women and men, 545 couples, attending a fertility clinic in Sweden during a two-year period. The Primary Care Evaluation of Mental Disorders (PRIME-MD), based on the Diagnostic and Statistical Manual of Mental Disorders, 4th edn (DSM-IV), was used as the diagnostic tool for evaluating mood and anxiety disorders. RESULTS Overall, 862 (79.1%) subjects filled in the PRIME-MD patient questionnaire. Any psychiatric diagnosis was present in 30.8% of females and in 10.2% of males in the study sample. Any mood disorder was present in 26.2% of females and 9.2% of males. Major depression was the most common mood disorder, prevalent in 10.9% of females and 5.1% of males. Any anxiety disorder was encountered in 14.8% of females and 4.9% males. Only 21% of the subjects with a psychiatric disorder according to DSM-IV received some form of treatment. CONCLUSIONS Mood disorders are common in both women and men undergoing IVF treatment. The majority of subjects with a psychiatric disorder were undiagnosed and untreated.